Applying the updated MRC framework for developing and evaluating complex interventions with integrated implementation conceptual knowledge: an example using NeuroRehabilitation OnLine - Connell, Louise; Ackerley, Suzanne; Rycroft-Malone, Jo (Frontiers in Health Services, 2025)
BackgroundThe updated 2021 UK Medical Research Council (MRC) Framework offers a valuable guide for implementation scientists to navigate the challenges of the development and evaluation of complex interventions. However, despite extensive citations, there is limited evidence of how the MRC Framework has been used in its entirety and limited integration with relevant implementation conceptual knowledge. To address this, we demonstrate the application of the updated MRC Framework incorporating implementation science frameworks, strategies, and outcomes. This example uses a telerehabilitation intervention, NeuroRehabilitation OnLine (NROL), implemented within an existing healthcare system.MethodsWithin a clinical-academic partnership, we completed the MRC Framework checklist, and the context was described using the updated Consolidated Framework for Implementation Research (CFIR). We used a deliberative process to operationalise the MRC phases: adaptation of NROL based on the ADAPT guidance and establishing the feasibility of NROL through concurrent implementation and evaluation. Phases are described in two iterations: within a single service and then when scaled up as a regional innovation. Stakeholders were involved throughout. Implementation strategies were identified using the CFIR-Expert Recommendations for Implementing Change (CFIR-ERIC) matching tool. Proctor's implementation outcomes were selected for the evaluation.ResultsThe MRC Framework provided a useful structure when applied iteratively to address key uncertainties for implementation. Stakeholder co-production was integral to all phases, in both iterations. An additional sustainment phase was added to the framework, reflecting that the value proposition discussions with decision-makers inevitably culminated in decision points. This guided decision-making for NROL to be scaled up. Logic Models were co-produced and iterated to depict programme theory and formalise the integration of implementation conceptual knowledge.ConclusionSynergistic in nature, the MRC Framework benefitted the conceptualisation of implementation through the use of its phases, and implementation science knowledge was useful in enacting the core elements within the MRC Framework. This example of application will be directly relevant to the field of rehabilitation and build transferable knowledge to enrich implementation research and practice.